REVITALIZATION AND ARRANGEMENT OF WATOE DELEAN TOURISM THROUGH THE CONCEPT OF DESTINATION BRANDING IN KEBON ALAS, SUKORENO, PRIGEN, PASURUAN - Muliatie, Yurilla Endah; Indrawati, Mei; Farid, Muchammad; Prasetyo, Kobin; Setiawan, Randy Putra; Siswanti, Liza Alif (STIE Pelita Nusantara, 2023)
The partner in this activity is POKMAS Guyup Rukun Dusun Kebonalas, Sukoreno Village, Prigen, chaired by Mr. Rofik Usmanto as Babinkamtibmas in Prigen. The daily organizer of the Watoe Delean is Mr. Subkan. The problems felt are not internal problems or problems with local residents because Watoe Delean was created based on initiative of residents who wanted tourist attractions in their area. The existing problems are more about facilities and marketing problems. This tourist attraction has actually been operating since 2019. Due to Covid-19, this tourist attraction only functions as a rest area for those who pass through this area on their way to Mojokerto or Pandaan. Because this place is relatively new, it is very natural that the existing facilities are still inadequate. However, water, electricity, prayer room and toilet facilities are available because these are requirements that must be met by the management who collaborates to manage the Perum Perhutani forest area. With the end of the Covid-19 pandemic, this tourist spot needs to be reorganized so that it can be used as a tourist spot in accordance with the original purpose of its establishment. So it is necessary to revitalize and organize, especially the existing facilities at this tourist spot. Promotion also required so that this place is visited by many tourists, both local and foreigners.